Implementation of Guided Inquiry Learning-Based Electronic Modules to Improve Student’s Analytical Skills - Muhammad Noris; Margiyono Suyitno; Setria Utama Rizal; Adin Lazuardy Firdiansyah; Sukamdi Sukamdi (Jurnal Penelitian Pendidikan IPA, 2023)
This type of research is Research and Development (R&D) with the 4D development model (Define, Design, Development, and Disseminate). The research subjects were 70 Grade VII students of SMPN, NTB. The results of the Guided Inquiry-based E-Module feasibility test ranged from 89.56% to the very feasible category. This shows that the E-Module can be used as an instrument or learning media. Meanwhile, the results of the practicality test of the E-Module based on Guided Inquiry Learning based on student responses ranged from 88.32% in the very practical category, while the teacher's responses ranged from 93.04% to the very practical category. The test results for the effectiveness of using the Guided Inquiry-based E-Module are shown by the Gain-Score obtained by students after using the E-Module. This can be seen from the Gain score obtained by the experimental class ranging from 78.03% which indicates that the media is quite effective in learning. This can be seen from the Asymp value. Sig. (2-Tailed) ranges from 0.000 <0.05, meaning that there is a significant difference in the analytic abilities of students using guided inquiry learning-based E-Modules.